THE RELATIONSHIP OF LOGOPEDIC DISORDERS WITH MALOCCLUSIONS - Kuroіedova, V.D.; Halych, L.B.; Halych, L.V.; Korobov, P.S. (World of Medicine and Biology, 2024)
Insufficient functioning of the speech apparatus leads to insufficient language practice in the most active period of speech development. The experiences associated with the awareness of one's defect and the negative reaction of others to the speech defect negatively affect the child's desire to communicate. This, in turn, affects speech development even more. Malocclusion also adversely affect the appearance and psyche of the patient. The purpose of this study was to identify speech therapy features in orthodontic patients with various types of malocclusion. An analysis of 536 case histories of orthodontic patients aged 5–30 years and 104 of them with speech disorders taking into account age, gender, orthodontic diagnosis, study of speech therapy status with statistical processing of the results was carried out. The most frequent speech therapy problems occurred with class I malocclusion according to Angle. The second and third places in terms of the frequency of impaired function of the articulatory apparatus are occupied by Angle II class and open bite, respectively. In patients with progenia, that is, with class III according to Angle, speech disorders were detected much less often. The obtained data indicate that in the 21st century, logopedic disorders become an important etiological factor in the occurrence of malocclusions. In the vast majority malocclusions are combined with complex dyslalia, which significantly complicate orthodontic treatment and lead to the recurrence of bite anomalies.
Keywords: ortodontics; teeth; jaws; anomalies; patients; allolalias